Análise multitemporal do uso da terra no projeto de assentamento São Francisco (Canutama/Am), frente às políticas nacionais de preservação ambiental - Barroso, Giovanna da Silva (Brasíl, 2024)
The analysis of spatial patterns and trends in deforestation in the Brazilian Amazon lacks a consistent and systematic empirical basis. Brazil has benefited enormously from advances in the field of remote sensing and satellite image processing over the last decade. The conservation of forests and other types of native vegetation is essential to protect the original fauna and flora of each region. Brazilian legislation contains, among the main instruments to ensure this conservation, the Permanent Preservation Area (APP) and the Legal Reserve (RL). The priority with public policies related to the environment in Brazil was observed by some authors from the 1970s onwards, as until that time Brazil was a country of economic production mainly focused on agriculture and livestock. It appears that public policies are essential for the realization of family farming and for its consolidation as a driver of a rural development policy. The objective of this research was to evaluate the multitemporal dynamics of deforested areas in 2005, 2010, 2015 and 2020, using spatial monitoring tools (ArcGis 10.8) and data available via the web, analyzing the results with public policies aimed at preserving the environment.